2021
DOI: 10.1177/03000605211017724
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dietary factors and recurrent aphthous stomatitis in China: a cross-sectional study

Abstract: Objective Recurrent aphthous stomatitis (RAS), a common oral mucosal disorder characterized by chronic, inflammatory, and ovoid ulcers, has a complex etiology. The purpose of the study was to investigate the specific dietary factors influencing the prevalence of RAS. Methods A total of 754 participants aged 18 to 59 years were enrolled in this descriptive cross-sectional study. An anonymous questionnaire was adopted to investigate the distribution of RAS, dietary factors, self-reported trigger factors, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In fact, we demonstrated that the proportion of smoking history in the relapse group showed a 100% increase compared with that in the no-relapse group, although no association was found in this study. The association was also not signi cant when stratifying by spicy food intake habit, consistent with a cross-sectional study of patients aged 18-59 years [12]. Recent research has hypothesized that intake of high-calorie fried and spicy food is a risk factor for RAS [10].…”
Section: Discussionsupporting
confidence: 83%
“…In fact, we demonstrated that the proportion of smoking history in the relapse group showed a 100% increase compared with that in the no-relapse group, although no association was found in this study. The association was also not signi cant when stratifying by spicy food intake habit, consistent with a cross-sectional study of patients aged 18-59 years [12]. Recent research has hypothesized that intake of high-calorie fried and spicy food is a risk factor for RAS [10].…”
Section: Discussionsupporting
confidence: 83%
“…Some of the vitamins and minerals found in vegetables and fruit function as antioxidants, and these can reduce the occurrence of disease or prevent the occurrence of lesions. 42 Predisposing factors for RAS caused by nutritional deficiencies when there are insufficient vegetables, fruits, and other foods in the diet can result in RAS. In this study, only limited questions related to predisposing factors for nutritional deficiency were asked.…”
Section: Discussionmentioning
confidence: 99%
“…167 Fruits, dairy products, vegetables and water in the diet have been proven to be the prevention factors of RAU, and the intake of fruit and water is inversely associated with the incidence rate of RAU. 168…”
Section: Recurrent Aphthous Ulcerationmentioning
confidence: 99%